Preliminary experience in laparoscopic distal pancreatectomy using the AEON™ endovascular stapler - Sheen, Aali J.; Bandyopadhyay, Samik; Baltatzis, Minas; Deshpande, Rahul; Jamdar, Saurabh; Carino, Nicola de Liguori (Frontiers in Oncology, 2023)
Background: To investigate the effects on pancreatic leak rates as well as other outcome measures with the use of a new innovative endovascular stapler, AEONTM. Methods: In a retrospective review of prospectively collected information stored on a secure tertiary unit registry, data from patients undergoing distal or lateral pancreatectomy was analysed for any differences on pancreatic fistula rates, length of stay, comprehensive complication index (CCI) as well as demographics. Statistical analysis was undertaken using Chi-square test or Fisher Exact test and numerical variables using One Way ANOVA test with significance defined as <0.05. Results: There were no differences in the demographics between the two groups which totalled 64 patients over two years from 2019 to 2021. 49 and 14 patients underwent pancreatic transection using other instruments and AEONTM endovascular stapler respectively. Comparing the two staplers there were significant differences with the AEONTM stapler demonstrating a reduced rate of mean drain lipase on postoperative day 3 with other instruments (3951 U/L) versus AEONTM (446 U/L) (p=0.017) (65% reduced to 20%), reduction in the mean CCI when AEONTM was used was 4.97, increasing to 13.16 when other instruments were used (p=0.089), a reduction in the mean length of stay was shorter by 4 days in the AEONTM group compared to the other devices (6 and 10 days respectively, p=0.014) Conclusion: AEONTM stapler when used to transect the pancreas has demonstrated great potential with preliminary results in its use depicting a significantly reduced pancreatic fistula rate, CCI as well as the length of stay in hospital. Its use should be further evaluated with an increase in numbers with the encouraging results likely to be related to the technology used in the design of the AEONTM stapler.